2020
DOI: 10.3390/ijms21197123
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase 1 and 2 Differentially Regulate Glucose Metabolism and Adipose Tissue Mitochondrial Respiration: Implications for Metabolic Dysregulation

Abstract: Heme oxygenase (HO) consists of inducible (HO-1) and constitutive (HO-2) isoforms that are encoded by Hmox1 and Hmox2 genes, respectively. As an anti-inflammatory and antioxidant molecule, HO participates in the development of metabolic diseases. Whether Hmox deficiency causes metabolic abnormalities under basal conditions remains unclear. We hypothesized that HO-1 and HO-2 differentially affect global and adipose tissue metabolism. To test this hypothesis, we determined insulin sensitivity, glucose tolerance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…The results showed that the GA content increased by 60.1% and 56.0% and decreased by 26.0%, while the enzymatic activity of HO increased by 57.1% and 18.1% and decreased by 15.8%, respectively [ 42 ]. In addition to fungi, HO was vital for modulating glucose and energy metabolism in mammals [ 43 ]. In this study, we speculated that HO could participate in the regulation of GA content through its catalytic product CO.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the GA content increased by 60.1% and 56.0% and decreased by 26.0%, while the enzymatic activity of HO increased by 57.1% and 18.1% and decreased by 15.8%, respectively [ 42 ]. In addition to fungi, HO was vital for modulating glucose and energy metabolism in mammals [ 43 ]. In this study, we speculated that HO could participate in the regulation of GA content through its catalytic product CO.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 has also been shown to reduce lipid accumulation and oxidative damage in mice with hepatic steatosis ( Upadhyay et al, 2020 ). Recent studies in humans have linked HMOX2, Nrf2, and IL-1β with insulin resistance and obesity ( Li et al, 2012 , 2020 ; Crilly et al, 2016 ; Tan et al, 2018 ; Yao et al, 2020 ), which are two characteristics exhibited by fasting NES ( Houser et al, 2013 ). Evidently, more research is needed to understand the link between CO and IL1B expression in diving, fasting-adapted mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Ключовим ензимом метаболічного шляху синтезу гему є δ-амінолевулінатсинтаза (КФ 2.3.1.37), що каталізує першу реакцію біосинтетичного шляху гему -конденсацію гліцину та сукциніл-коензиму А з утворенням δ-амінолевулінової кислоти [10]. Гемоксигеназа (КФ 1.14.99.3)ключовий ензим деградації гему -забезпечує окисне розщеплення гему з утворенням в еквімолярній кількості монооксиду карбону (СО) та білівердину, що розглядаються як цитопротекторні молекули [11,12].…”
Section: вступunclassified